Revisiting hypertension prevalence and risk factors: prevalence of hypertension and risk of diabetes in China - Qiuting Jia; Yanbing Pan; Yan Zhang; Haiyu Zhang; Yanzi Zhang; Yongle Wang; Yihui Kong (BMC Cardiovascular Disorders)
Abstract Background Hypertension is a common and serious public health issue, with elevated blood pressure significantly increasing the risk of cardiovascular disease and diabetes. In adults, blood pressure values of 130–139 mm Hg/80–89 mm Hg are associated with an increasing relative risk of cardiovascular complications and mortality. According to the American College of Cardiology (ACC) / American Heart Association (AHA) criteria for the diagnosis of hypertension, this study aimed to describe the prevalence and risk factors for stage 1 (systolic blood pressure 130–139 mm Hg or diastolic blood pressure 80–89 mm Hg) and stage 2 (systolic blood pressure ≥ 140 mm Hg or diastolic blood pressure ≥ 90 mm Hg) hypertension. Second, to evaluate the effect of different hypertension grades on the incidence of diabetes. Methods Data were obtained from the DATADRYAD database. This study included 32,625 adults from 32 regions in 11 cities in China, enrolled between 2010 and 2016, who were free of diabetes at baseline. Logistic regression was used to assess the risk factors for different grades of hypertension. Cox proportional hazard regression analysis was performed to explore the relationship between stage 1 and stage 2 of hypertension and diabetes. All data were analyzed using the SAS 9.4 software and R software (version 4.2.2). Results The study showed that the prevalence of stage 1 and stage 2 hypertension was higher, and the prevalence of stage 1 was higher than stage 2 hypertension. Sex, age, body mass index (BMI), fasting plasma glucose, triglycerides, and alanine aminotransferase (ALT) were the risk factors for stage 1 hypertension, and sex, age, BMI, cholesterol, triglycerides, ALT, and alcohol drinking were risk factors for stage 2 hypertension. In addition, our study demonstrated a significant interaction between age and sex, BMI and sex on the risk of hypertension, respectively. Furthermore, the higher the blood pressure, the higher the risk of developing diabetes. Conclusions These findings highlight the importance of paying attention not only to individuals with stage 2 hypertension but also to those with stage 1 hypertension, given the elevated risk of diabetes associated with both.